2023
DOI: 10.3390/ijerph20085544
|View full text |Cite
|
Sign up to set email alerts
|

Recommending Physical Activity for People with Intellectual Disabilities: The Relevance of Public Health Guidelines, Physical Activity Behaviour and Type of Contact

Abstract: People with an intellectual disability (ID) often exhibit more sedentary behaviour and are less physically active than the general population. While previous public health guidelines on physical activity (PA) did not specifically address the needs of people with an ID, the recent updates now include this population, with recommendations similar to those for the general population. However, it is unclear whether the information about these guidelines has reached the broader public and what factors may influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Disabled people are overwhelmingly less physically active compared to their typical peers, which entail a variety of adverse physical consequences (Aksović et al, 2023;Kreinbucher-Bekerle et al, 2023). The outcomes of this idleness manifest in various secondary conditions; we mention cardiovascular disease, i.e., most prevalent cause of death among these people (Forman-Hoffman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Disabled people are overwhelmingly less physically active compared to their typical peers, which entail a variety of adverse physical consequences (Aksović et al, 2023;Kreinbucher-Bekerle et al, 2023). The outcomes of this idleness manifest in various secondary conditions; we mention cardiovascular disease, i.e., most prevalent cause of death among these people (Forman-Hoffman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…First, increasing the physical activity of people with severe-to-profound intellectual and multiple disabilities is a valued objective of rehabilitation and care contexts that may have important health implications [5,6,12]. Pursuing this objective through the use of interactive technology may be considered profitable and convenient for at least two basic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that people with intellectual or multiple disabilities (e.g., combinations of intellectual disability and motor or sensory impairments), tend to have low levels of physical activity compared to their typical peers [1][2][3][4][5]. A low level of physical activity is generally considered responsible for a variety of adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Disabled people are significantly less physically active than their typical peers, which can lead to a variety of adverse health consequences [13,31]. The outcomes of this idleness manifest in several secondary diseases, among which cardiovascular disease, i.e., the first cause of death among these persons [20].…”
Section: Discussionmentioning
confidence: 99%